2015
DOI: 10.1002/anie.201503373
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Intramolecular Aminofluorination, Oxyfluorination, and Carbofluorination with a Stable and Versatile Hypervalent Fluoroiodine Reagent

Abstract: Application of a fluoroiodine analogue of the Togni reagent was studied in fluorocyclization reactions. In the presence of a transition-metal catalyst the applied fluoroiodine reagent can be used for aminofluorination, oxyfluorination, and carbofluorination reactions. The described procedure has a very broad synthetic scope for preparation of functionalized hetero- and isocyclic compounds having a tertiary fluorine substituent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(58 citation statements)
references
References 84 publications
1
54
0
1
Order By: Relevance
“…In 2015, Szabo and Yuan reported the first fluorinative cyclization of alkenes using benziodoxole 22 (Scheme 15). [43] In this process, piperidine 74, pyrollidine 75, cyclic ether 76 and cyclopentane 77 could be obtained in 62-76% yield. In the case of amine and oxygen nucleophiles, zinc(II) tetrafluoroborate was used as catalyst, whereas a copper catalyst was better for carbon nucleophiles.…”
Section: Scheme 13 Dihalogenation and Oxybromination Of Olefinsmentioning
confidence: 97%
“…In 2015, Szabo and Yuan reported the first fluorinative cyclization of alkenes using benziodoxole 22 (Scheme 15). [43] In this process, piperidine 74, pyrollidine 75, cyclic ether 76 and cyclopentane 77 could be obtained in 62-76% yield. In the case of amine and oxygen nucleophiles, zinc(II) tetrafluoroborate was used as catalyst, whereas a copper catalyst was better for carbon nucleophiles.…”
Section: Scheme 13 Dihalogenation and Oxybromination Of Olefinsmentioning
confidence: 97%
“…Initial experiments showed that there was indeed ab eneficial effect of anisole (12)c ompared to the additive-free reaction (entries 1-4), but only at ad efined excesso ft hree equivalents of 12:T he amount of scavenger is probablyn ot sufficient at two equivalents (entry 2), and anisole( 12)m ight start to competea sa na ryl radicala cceptora ta na mount of four equivalents (entry 4), [18] so that lower yields are obtained in that case, too. As light improvement was achieved through incomplete degassing, whichleaves traces of oxygen in the reaction mixture (entry 5).…”
Section: Resultsmentioning
confidence: 99%
“…With optimized conditions available, we next evaluated the effect of anisole (12)i nc arbofluorination reactions starting from other arylhydrazines 5a-g and alkenes 6a-e (Scheme3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This cyclic fluoro iodane 21 combines the advantages of the linear difluoro iodoarenes, such as their unique fluorination reactivity, with ease of handling, contributing to their air and moisture stability. Besides the application of 21 in ‘standard’ fluorine chemistry, such as monofluorination of 1,3‐dicarbonyls and fluorocyclizations, chemoselective fluorinations of stilbenes have been developed. In 2014, Szabó and co‐workers reported the gem ‐difluorination of alkenes 20 in the presence of 21 and AgBF 4 (Scheme ) .…”
Section: Halogenations Using Hypervalent Iodine(iii) Reagentsmentioning
confidence: 99%